A preeminent gel blending polymer electrolyte of poly(vinylidene fluoride-hexafluoropropylene) -poly(propylene carbonate) for solid-state lithium ion batteries. (10th February 2019) - Liang, Y.F.; Xia, Y.; Zhang, S.Z.; Wang, X.L.; Xia, X.H.; Gu, C.D.; Wu, J.B.; Tu, J.P.
Abstract: A compositive synthesis of gel polymer electrolytes by blending poly(propylene carbonate) (PPC) into poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) as a polymer host is proposed. The blending polymer is produced by a facile solution casting method and ester groups of PPC are successful introduced into PVDF-HFP. The gel polymer electrolyte displays an excellent ion conductivity of 1.18 × 10 −3 S cm −1, broad electrochemical window up to 4.8 V (vs. Li/Li + ) and outstanding electrochemical stability within rechargeable lithium batteries at room temperature. The improvement of ion conductivity is attributed to the decrease of polymer crystallizability and the increase of micro pores. The strategy of blending is promising for the modification of PVDF-HFP electrolyte and foreground application in next-generation solid energy conversion devices.